2006
DOI: 10.1152/japplphysiol.00393.2006
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated gastric distress but no benefit to performance with adaptation to octanoate-rich esterified oils in well-trained male cyclists

Abstract: lands. Attenuated gastric distress but no benefit to performance with adaptation to octanoate-rich esterified oils in well-trained male cyclists. J Appl Physiol 101: [1733][1734][1735][1736][1737][1738][1739][1740][1741][1742][1743] 2006. First published July 13, 2006; doi:10.1152/japplphysiol.00393.2006.-We investigated the effects of modifying a normal dietary fatty acid composition and ingestion of high-fat exercise supplements on gastrointestinal distress, substrate oxidation, and endurance cycling perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
3
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 36 publications
3
32
3
1
Order By: Relevance
“…Meanwhile, the finding of an attenuated response to the intervention relative to the male cohort studied previously (Thorburn, Vistisen et al 2006) is consistent with the generalization that trained females respond with lower amplitude to nutritional-exercise unpublished), carbohydrate loading, and creatine supplementation .…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Meanwhile, the finding of an attenuated response to the intervention relative to the male cohort studied previously (Thorburn, Vistisen et al 2006) is consistent with the generalization that trained females respond with lower amplitude to nutritional-exercise unpublished), carbohydrate loading, and creatine supplementation .…”
Section: Discussionsupporting
confidence: 82%
“…In male subjects, we (Thorburn, Vistisen et al 2006) previously observed a clear substantial reduction in gastrointestinal distress parameters with MCFA adaptation; and in the covariate analysis, nausea had a moderate-strong reducing effect on sprint mean power. Conversely, in the current cohort of female subjects MCFA adaptation did not clearly attenuate gastrointestinal distress symptoms, and performance was not adversely affected by the intervention relative to the smallest worthwhile detriment in mean power (Table 1), or in relation to the distress marker nausea (Figure 3).…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations